A Novel CNTNAP2 Mutation Results in Abnormal Neuronal E/I Balance - Lu, Ping; Wang, Fengpeng; Zhou, Shuixiu; Huang, Xiaohua; Sun, Hao; Zhang, Yun-Wu; Yao, Yi; Zheng, Honghua (Frontiers in Neurology, 2021)
CNTNAP2 (coding for protein Caspr2), a member of neurexin family, plays an important role in the balance of excitatory and inhibitory postsynaptic currents (E/I balance). Here, we describe a novel pathogenic missense mutation in an infant with spontaneous recurrent seizures (SRSs) and intellectual disability. Genetic testing revealed a missense mutation c.2329 C>G (p. R777G) in the CNTNAP2 gene. To explore the effect of this novel mutation, primary cultured neurons were transfected with wild type homo CNTNAP2 or R777G mutation and the morphology and function of neuron were evaluated. When compared with the vehicle control group or wild type group, the neurites and the membrane currents, including spontaneous excitatory postsynaptic currents (sEPSCs) and inhibitory postsynaptic currents (sIPSCs), in CNTNAP2 R777G mutation group were all decreased or weakened. Moreover, the action potentials (APs) were also impaired in CNTNAP2 R777G group. Therefore, CNTNAP2 R777G may lead to the imbalance of excitatory and inhibitory postsynaptic currents in neural network contributing to SRSs.